Prevalence and Risk Factors of Sarcopenia in Patients with Dizziness. Issue 9 (27th October 2022) - Kamo, Tomohiko; Ogihara, Hirofumi; Tanaka, Ryozo; Kato, Takumi; Azami, Masato; Tsunoda, Reiko; Fushiki, Hiroaki
Abstract : Objective: This study aimed to investigate the prevalence of sarcopenia and factors associated with sarcopenia in patients with dizziness. Study Design: This is a cross-sectional study. Patients: A total of 162 patients 65 years or older with the chief complaint of dizziness or vertigo (dizziness group) and 132 community-dwelling elderly (control group) were recruited during their visit to the otolaryngology clinic between May 2020 and October 2021. Results: Of the 162 patients with dizziness (dizziness group), 53 (32.7%) were classified as sarcopenia according to the 2019 criteria of the Asian Working Group for Sarcopenia. There were significant differences in the prevalence of sarcopenia between the dizziness group and the control group ( p < 0.01). The factors that significantly affected the sarcopenia, in order of greater odds ratio, were HADS_A, age, and DHI_Total (odds ratio = 1.223, 1.130, and 1.022, respectively). Conclusions: The present study shows that (i) the prevalence of sarcopenia in patients with dizziness is higher than a community-dwelling elderly; (ii) patients with dizziness and sarcopenia have higher DHI_functional, DHI_emotional, DHI_total, and HADS_A compared with patients with dizziness but without sarcopenia; and (iii) age, HADS_A, and DHI were associated with sarcopenia in patients with dizziness.